Consumer Behavior of Muslim Minorities in Purchasing Halal Products: A Maslahah Perspective - Al Farisi, Muhammad Salman; Mahadewi, Erlina Puspitaloka; Khalid, Nour; Ratnawati, Aryanti; Erlangga, Heri; Wahid, Hariyaty Ab (IAIN Manado, 2024)
This study aims to analyze whether the consumption of halal products has a different priority scale based on maslahah orientation. This study is qualitative. The study was located in one of the minority Muslim areas in Indonesia. In this study the object of the study was the minority Muslim community of Indonesia who are Muslim and have purchased halal products. The research data were obtained based on interviews with the minority Muslim communities in Indonesia, namely Denpasar and Gianyar in Bali Province and Kupang East Nusa Tenggara Province, who are Muslim and have purchased halal products. This study's results indicate that consumers' behavior toward halal products regarding maslahah is included in the maslahah tahsiniyah or tertiary needs, namely, needs to be needed by humans to make life more comfortable and beautiful. Maslahah tahsiniyah is a complementary or complementary maslahah in the form of breadth and propriety that can complement the previous maslahah or maslahah hajiyah. If this problem is not met, human life will be less beautiful, but it does not cause harm. This study proves that the motivational characteristics of minority Muslim consumers in consuming halal products that have a priority scale of maslahah are tahsiniyah to obtain maximum benefits from halal products that do not only focus on the aspect of beauty, but also pay attention to the aspects of halal, cleanliness, and environmental friendliness.